2022
DOI: 10.1093/immadv/ltac015
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and adipose tissue impact on T-cell response and cancer immune checkpoint blockade therapy

Abstract: Many different types of cancer are now well-known to have increased occurrence or severity in individuals with obesity. The influence of obesity on cancer and the immune cells in the tumor microenvironment has been thought to be a pleiotropic effect. As key endocrine and immune organs, the highly plastic adipose tissues play crucial roles in obesity pathophysiology, as they show alterations according to environmental cues. Adipose tissues of lean subjects present mostly anti-inflammatory cells that are crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…IL-33 binds to IL-33 receptors on Treg cells and, together with PPAR- γ , promotes a Treg signature and immune and metabolic homeostasis. A Treg signature in lean SAT promotes non-shivering thermogenesis via increased UCP-1 and beigeing of WAT [ 113 ].…”
Section: Inflammation and Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-33 binds to IL-33 receptors on Treg cells and, together with PPAR- γ , promotes a Treg signature and immune and metabolic homeostasis. A Treg signature in lean SAT promotes non-shivering thermogenesis via increased UCP-1 and beigeing of WAT [ 113 ].…”
Section: Inflammation and Metabolismmentioning
confidence: 99%
“…Obesity results in the phosphorylation of PPAR- γ and the disappearance of Tregs and the suppression of adipogenesis in VAT [ 113 ]. There is a transition from the M2 to the M1-like macrophage phenotype in the ATM of obese individuals, which is mediated by adipocyte exosomes, NF- κ B, cyclooxygenase (COX)-2, Toll-like receptor (TLR) and Notch signalling pathways [ 73 , 109 ].…”
Section: Inflammation and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual meta-analyses confirmed that obesity is an independent risk factor worsening both the morbidity and severity of lung cancer [ 2 , 3 ]. On the other hand, obese patients respond much better to immunotherapy based on immune checkpoint inhibitors, which is another example of the obesity paradox [ 4 ]. According to the presented thesis, the relationship between obesity and lung cancer immunology seems unclear.…”
mentioning
confidence: 99%
“…Obesity is an independent risk factor for lung cancer development and is associated with increased tumor growth and aggressiveness. On the other hand, obesity is associated with improved response to cancer immunotherapy [ 4 ]. This result leads to the hypothesis that obese lung cancer patients should have a higher level of PD-1L expression compared to normal-weight patients.…”
mentioning
confidence: 99%